PENGGUNAAN MEDIA INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) UNTUK MENGINTENSIFKAN PEMBELAJARAN BAHASA INGRIS DI LUAR KELAS - Safnil Arsyad (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2016)
The facts show that the results of teaching and learning of English in Inggris at all levels are not yet satisfying because the students get very little chances to practice the language in the classroom while the learning acitivies outside the classroom are not yet extensive and to some extent are impossible. Although teachers have been retrained again and again, the curriculum has been renewed several times and the textbooks have been revised, the English learning results do not seem to show a significant improvement. This paper is trying to offer a possible solution for the problem; that is to use ICT based English lerning materials to intensify the student’s English learning activities outside the classroom particularly for university students. Thus, through more interactive and interesting learning activities outside the classroom using ICT media already available with the students such as smartphone, laptop or portable computer, the students will get more comprehensible language input.